Pengembangan Media Capcut Untuk Pembuatan Video Pembelajaran - Ajie Hariyadi; Andry Wirawan; Danti Dahlia; Zulfitria Zulfitria (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2026)
This research is motivated by the importance of using innovative and engaging learning media to increase elementary school students' motivation across all disciplines. The elementary learning process often requires strong visualizations to facilitate understanding of abstract material. This research aims to develop video-based learning media using the CapCut application that can be applied to all subjects, including Mathematics, Science, Social Studies, Indonesian Language, and Pancasila Education. The research method used is Research and Development (Research and Developmentor R&D) with the ADDIE model (Analysis, Design, Development, Implementation, EvaluationThe subjects of this study were teachers and upper-grade students at an elementary school. Data collection instruments were conducted through interviews, expert-validated questionnaires, and student and teacher response questionnaires. The research results show that the development of learning videos using CapCut was deemed highly feasible by media experts and content experts. Furthermore, the use of these videos proved effective in increasing student enthusiasm and understanding of the subject matter. The study concluded that CapCut-based learning videos are highly practical, flexible, and suitable for use as teaching aids for teachers across all disciplines in elementary schools.